1999
DOI: 10.1046/j.1365-2133.1999.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

A rational approach to melanoma follow-up in patients with primary cutaneous melanoma

Abstract: From the Scottish Melanoma Group database for south-east Scotland we evaluated 5-year follow-up in patients with cutaneous malignant melanoma excised between 1979 and 1994 and devised an 'evidence-based' review protocol. Of the 1568 with stage I melanoma, 293 (19%) developed a recurrence, 32 had a second primary melanoma and 97 had an in-situ melanoma. The disease-free interval shortened progressively with increasing tumour thickness. Overall, 80% of recurrences were within the first 3 years, but a few patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 21 publications
3
58
1
3
Order By: Relevance
“…In patients attending the FU I/II program, about 68% of first relapses were detected due to scheduled follow-up activity. This is a significantly higher yield than reported by Dicker et al (1999) who found only 26% of first recurrences detected at the follow-up clinic. Baughan et al (1993), Kersey et al (1985) as well as Bassères et al (1995) found 41, 44 and 50%, respectively, of all first relapses to be detected by routine follow-up activity considering only the purely doctor-diagnosed recurrences.…”
Section: Follow-up Stage I/iicontrasting
confidence: 47%
“…In patients attending the FU I/II program, about 68% of first relapses were detected due to scheduled follow-up activity. This is a significantly higher yield than reported by Dicker et al (1999) who found only 26% of first recurrences detected at the follow-up clinic. Baughan et al (1993), Kersey et al (1985) as well as Bassères et al (1995) found 41, 44 and 50%, respectively, of all first relapses to be detected by routine follow-up activity considering only the purely doctor-diagnosed recurrences.…”
Section: Follow-up Stage I/iicontrasting
confidence: 47%
“…[588][589][590][600][601][602][603]. Median occurrence of regional lymph node metastases was earlier than in locoregional or distant metastases (recurrence-free survival 17.6 months vs. 23, respectively 25.9 months) [604].…”
Section: Background Information On the Clinical Decision Processmentioning
confidence: 99%
“…Depending on tumor thickness, the majority of recurrences even in thin melanomas (< 1.0 mm), occurred within the first years after primary diagnosis [590,596,599]. The risk for recurrence after 10 years is roughly 1 % [588].…”
Section: Background Information On the Clinical Decision Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison melanomas of >1.5mm have a greater risk of recurrence in the first year following a diagnosis. This then decreases to below 2% after the first 5 years (83)(84)(85). Across all melanoma stages approximately 80% of recurrences will occur in the first 3 years (83,86,87).…”
Section: Discussionmentioning
confidence: 99%